Improving Students' Speaking Skills by Conducting Small Group Discussions in Grade 8 Smpn 14 Bintan - Diah Khotimah Ruba'i; Nainggolan Elsa Ernawati; Muhammad Candra (Universitas Maritim Raja Ali Haji (UMRAH), 2022)
This study aimed to describe how small group discussions improved students' speaking skills in class VIII of SMPN 14 Bintan. The method used in this research is classroom action research (CAR). The population in this study were all class VIII C of SMPN 14 Bintan students in the 2021/2022 academic year, consisting of 28 students. The data was collected through pre-test and post-test. In the first test (pre-test), the number of students who met the minimum completeness criteria of 75 was 1 out of 28 students (5%). In the second test (post-test I), students who scored above 75 or met the minimum completeness criteria were 7 out of 28 students (25%). In the third test (post-test II), 16 of 28 students (57.14%) met the minimum completeness criteria of 75. The result shows that there are some improvements in the students' speaking skills quantitatively and qualitatively. Moreover, students were more active and participated in the teaching and learning process of speaking. To conclude, the SGD worked excellently and efficiently in helping students speak English in the eighth grade of SMPN 14 Bintan.